MONITORING THE TECHNICAL CONDITION OF THE BALL BEARING BY METHODS OF VIBRATION AND THERMAL IMAGING DIAGNOSTICS (Nonconventional Technologies Review, 2021)
Bearings are now part of most small or large rotary machines. Maintenance of rotary machines is an essential part of preventing a bearing seizure, which can cause extensive damage to the machine or injury to the machine operators. Early replacement of a broken bearing can preserve the machine, avoiding long-term downtime and saving considerable amounts of money. This paper is concerned with the measurement of two vibration parameters (velocity and acceleration of vibrations) on the bearing housing of a laboratory model using a worn and unworn bearing. The measurement also focuses on monitoring the temperature change in the bearings using a thermal imager. Subsequent analysis of the vibrodiagnostic signal and thermal imaging pictures from the bearing is critical in terms of early identification of an upcoming failure, which can result in the failure of the production equipment.
Keywords: Diagnostics; laboratory model; measurement; evaluation; bearing; temperature; vibrations